On orientational order in nematic and twist-bend nematic phases: a 2H-NMR study of binary mixtures of the odd dimer, 1″, 9″-bis(4-cyanobiphenyl-4′-yl) nonane, (CB9CB), and the monomer, 4-pentyl-4′-cyanobiphenyl, (5CB-d2). Issue 13 (8th December 2018) - Luckhurst, Geoffrey R.; Timimi, Bakir A.; Wells, Neil J.; Zimmermann, Herbert
ABSTRACT: In this article, we explore those factors that influence the orientational order in both nematic and twist-bend nematic phases. The systems used for our NMR experiments are binary mixtures of a dimer and a related monomer thus enabling its behaviour to be controlled continuously, through its composition rather than chemical structure. Earlier studies have revealed that as the temperature is lowered in the nematic phase, the orientational order frequently passes through a maximum prior to the formation of the NTB phase. A confirmative indication of this unusual behaviour is that the Haller function cannot fit this dependence over the entire nematic range; such behaviour is intriguing. In the NTB phase, the measured order parameter is often insensitive to decreasing temperature for systems with strong NTB –N transitions often associated with a narrow nematic range. For those mesogens with longer nematic ranges and hence weaker NTB –N transitions, the order parameter decreases more markedly with temperature. As expected for the weak transitions, the behaviour of the order parameter is observed to be essentially continuous across the transition. Associated with the orientational order in the NTB phase is the conical angle and an off-diagonal element of the Saupe ordering matrix. Graphical Abstract: